Food literacy of selected students in the University of the Philippines Diliman - Babon, Angelica O.; Trinidad, Mary Justine Clarise A. (Quezon City University of the Philippines Diliman, 2025)
As food plays an important role in one's health and university students are at high risk for nutritional problems, the researcher created a Food Literacy Scale following the model of Vidgen and Gallegos (2014) to determine the food literacy level of university students and the factors that influence it. Data were gathered through survey methodology and were analyzed using multiple linear regression. The analysis revealed that the food literacy level of the selected university students from the University of the Philippines Diliman is high (M = 115.95). Among the eight variables analyzed, the only significant factor in food literacy is the frequency of involvement in food planning and preparation (p = .000). The scores in each domain vary, with the "plan and manage" and "eat" domains having high mean scores (M = 32.26 and M = 28.40, respectively), while the "select" and "prepare" domains having average mean scores (M = 27.55 and M = 27.75, respectively). For the "plan and manage" (p = .000), "select" (p = .001), and "eat" (p = .001) domains, the only significant predictor is the frequency of involvement in food planning and preparation, whereas both the degree program (p = .044) and the frequency of involvement in food planning and preparation (p = .000) affect the "prepare" domain. The factors with significant influence were subjected to dichotomous analysis. The analysis revealed that even when examined without the other factors, frequency of involvement in food planning and preparation remains a significant predictor (p < .05) of all the four domains and the overall food literacy, and degree program remains a significant predictor (p = .012) for the "prepare" domain. The results indicate that university students have strong food-related knowledge and skills. While they demonstrate effective meal planning, food resource management, and healthy eating habits, students only show moderate proficiency in the selection of food products and basic food preparation skills.
In partial fulfillment for the Degree of Bachelor of Science in Home Economics
Thesis
Keywords: Nutrition -- Philippines; College students -- Health and hygiene; Nutrition -- Study and teaching; Public health; College students -- Nutrition; Food literacy; Food literacy scale